Teorias implícitas: o ensinar e o aprender na formação inicial de professores de física - Walter, Vinícius Galvan (2025)
The initial teacher education plays a fundamental role in consolidating pedagogical practices that promote active learning. However, despite guidelines encouraging constructivist approaches, many pre-service physics teachers still adopt traditional methods when planning their lessons. This contrast between theoretical training and teaching practice highlights the need to investigate future teachers' pedagogical beliefs and understand how their conceptions influence their methodological choices. In this context, this study analyzes the implicit theories of pre-service physics teachers, investigating how their conceptions of teaching and learning impact lesson planning. Thus, the research is guided by the following question: What are the implicit theories of Physics Licentiate students at UFMS regarding teaching and learning? The analysis of these conceptions allowed us to understand how future teachers articulate theory and practice, as well as to indicate ways to improve teacher education. This qualitative study was conducted with ten students from the Physics Licentiate program at UFMS, within the course Tópicos Especiais IV, offered by the Institute of Physics. Data collection involved the use of dilemma-based questionnaires, semi-structured interviews, and an analysis of the lesson plans developed by the participants. The data were analyzed through Content Analysis, enabling the categorization of the students' conceptions based on the Implicit Theories of Teaching and Learning: Direct Theory, Interpretative Theory, and Constructive Theory. The results revealed that, although pre-service teachers recognize the importance of student-centered and active methodologies, many still struggle to implement them in their teaching practice. These difficulties are often linked to deeply rooted beliefs, influenced by their schooling experiences, pre-school experiences, and other factors. Furthermore, we observed that the implicit theories expressed by the students directly impact their methodological choices, demonstrating that their learning conceptions determine the strategies adopted in physics teaching. These findings highlight the need for an initial teacher education that provides practical experiences aligned with constructivism, helping pre-service teachers to overcome traditional conceptions and adopt more innovative pedagogical practices.